2014
DOI: 10.2214/ajr.13.12028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Centering on Patient Dose and Image Noise in Chest CT

Abstract: Regardless of patient size, most patients in this study were positioned too low, which negatively affected both patient dose and image noise. Miscentering was more pronounced in smaller pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
81
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 23 publications
8
81
2
Order By: Relevance
“…8,9,14 Another trend observed was the increased sensitivity of the 0°localizer angle to phantom movement compared with 90°localizer angle, supporting previous research. 9 One would expect the 0°localizer angle to be more sensitive to vertical movement as the projected area of the phantom changes, and correspondingly, the 90°localizer angle to be more sensitive to horizontal movement. This was confirmed, although when accounting for all vertical and horizontal movement, greater variations in the CTDIvol were observed for the 0°source angle acquisitions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…8,9,14 Another trend observed was the increased sensitivity of the 0°localizer angle to phantom movement compared with 90°localizer angle, supporting previous research. 9 One would expect the 0°localizer angle to be more sensitive to vertical movement as the projected area of the phantom changes, and correspondingly, the 90°localizer angle to be more sensitive to horizontal movement. This was confirmed, although when accounting for all vertical and horizontal movement, greater variations in the CTDIvol were observed for the 0°source angle acquisitions.…”
Section: Discussionsupporting
confidence: 83%
“…9,14 This can be explained in terms of the phantom moving towards the X-ray source, thus having a greater magnification in the projection image and being interpreted by the scanner as a larger body requiring a higher tube current. 14 The CTDIvol shows little dependence on table height for the 90°l ocalizer plane, as although the phantom is moving vertically in these radiographs, its projected size remains largely unchanged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons are changes in tube current-time product (e. g. by affecting the function of the automatic exposure control system), an increase of radiation dose absorbed by sensitive surface tissues, or an altered projection of organs onto the bowtie filter [24,27]. It was shown that already relatively small aberrations in vertical position of 2 -6 cm may result in dose increases of up to 51 % [25,26]. As patient centering is a user-specific factor and therefore controllable, we performed an in-service training for our radiographers pointing out the importance of proper patient positioning and the need to refresh their skills.…”
mentioning
confidence: 99%
“…However, a mean working experience of 8.32 years indicates that most radiographers involved in the study were well versed. (2) We used scanners from a single vendor, which may have affected dose values as, for example, tube current modulation techniques and bowtie filters vary among different vendors [25]. (3) In some patients alerts may have been caused by more than one source or an interaction of several causes (e. g. high BMI and off-centering).…”
mentioning
confidence: 99%